Differential expression profile of plasma exosomal microRNAs in acute type A aortic dissection with acute lung injury - Chiyuan Zhang; Hui Bai; Lei Zhang; Yanfeng Zhang; Xuliang Chen; Ruizheng Shi; Guogang Zhang; Qian Xu; Guoqiang Lin (Scientific Reports, 2022)
Abstract MicroRNAs (miRNAs) packaged into exosomes mediate cell communication and contribute to the pathogenesis of acute type A aortic dissection (ATAAD) with acute lung injury (ALI). The expression profile of plasma exosomal miRNAs in ATAAD patients with ALI hasn’t been identified. We performed a miRNA-sequencing to analyze the differentially expressed miRNAs (DE-miRNAs) of circulating exosomes in ATAAD patients with ALI compared to patients without ALI, founding 283 specific miRNAs in two groups. We respectively selected the top 10 downregulated and upregulated DE-miRNAs for further studies. The predicted transcription factors (TFs) of these DE-miRNAs were SMAD2, SRSF1, USF1, etc. The Gene Ontology (GO) and Kyoto Encyclopedia Genes and Genomes (KEGG) analysis predicted their target genes mainly involved acute inflammatory response, cell junction, cytoskeleton, NF-κB signaling pathway, etc. Construction and analysis of the PPI network revealed that RHOA and INSR were considered hub genes with the highest connectivity degrees. Moreover, we confirmed two exosomal miRNAs (hsa-miR-485-5p and hsa-miR-206) by real-time quantitative polymerase chain reaction (RT-qPCR) in a validation cohort. Our study identified a plasma exosomal miRNAs signature related to ATAAD with ALI. Certain DE-miRNAs may contribute to the progression of this disease, which help us better understand the pathogenesis of ATAAD with ALI.